Produtividade em espécies de Drosophila do subgrupo saltans (grupo saltans, subgênero Sophophora): efeitos da infecção por Wolbachia em linhagens normais e introgredidas - Patarro, Thais de França [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Reproductive isolation mechanisms are agents that prevent or decrease the exchange of genes between species or populations of the same species that are in process of speciation. These mechanisms are comprised of a series of processes operating at different levels of reproduction, ranging from pre-zygotic to post-zygotic barriers. In recent decades, studies have indicated that the absence of progeny can also be promoted by interactions of symbiont microorganisms and their hosts. Presently, the most known endosymbionts capable of interact with the insects, interfering in the reproductive process, are the alphaproteobacteria of the genus Wolbachia. In the present study, we investigated the Wolbachia effects on reproduction, focusing the parameter productivity (number of progeny) in crosses involving four strains of Drosophila saltans and D. prosaltans (close species belonging to the saltans group, Sophophora subgenus) and two introgressed strains started with F1 hybrids of these two species. Preliminary tests for screening Wolbachia showed that each of the six strains was infected with one strain of the symbiont. The results on productivity were obtained from intra and intercrosses of the strains in the conditions infected or uninfected. The elimination of Wolbachia was performed by treatment of the strains with the antibiotics tetracycline. The main mechanism resulting from the interaction symbiont-host described in the literature is called cytoplasmatic incompatibility (CI) and occurs in the intercrosses of uninfected females with infected males. It is considered that, in infected males, there are changes in the sperm that only the oocytes of infected females are able to correct, reestablishing the productivity. The present results on Wolbachia infection of the species from the saltans group were variable. In several crosses of the strains, the combinations that are sterile or almost sterile when CI effect occurs, were the most productive ...

Mecanismos de isolamento reprodutivo são agentes que impedem ou diminuem a troca de genes entre duas espécies ou populações de uma mesma espécie que se encontram em processo de especiação. Esses mecanismos são compreendidos por uma serie de processos que atuam em diferentes níveis da reprodução, incluindo desde barreiras pré-zigóticas até barreiras pós-zigóticas. Nas ultimas décadas, muitos estudos têm indicado que a ausência de híbridos pode também ser promovida por interações entre microorganismos simbiontes e seus hospedeiros. Um dos principais simbiontes capazes de interagir com os insetos, levando a modificações do processo reprodutivo, são as alfaproteobactérias do gênero Wolbachia. No presente estudo, foram analisados os efeitos da infecção pela Wolbachia causados no parâmetro produtividade (número de descendentes), em intra e intercruzamentos de linhagens de Drosophila. saltans, D. prosaltans (espécies próximas pertencentes ao subgrupo saltans) e mais duas linhagens, obtidas por introgressão a partir de híbridos F1 do intercruzamento dessas duas espécies. Análises preliminares para detecção da infecção pela Wolbachia nas linhagens de Drosophila mostraram que cada uma das seis linhagens estava infectada com uma linhagem do simbionte. Os resultados quanto à produtividade foram obtidos de intra e intercruzamentos das linhagens nas condições infectadas e não infectadas A eliminação do simbionte foi realizada por tratamento com o antibiótico tetraciclina. O principal mecanismo resultante da interação simbionte-hospedeiro mencionado na literatura é chamado incompatibilidade citoplasmática (IC) e ocorre nos intercruzamentos de fêmeas não infectadas com machos infectados. Considera-se que nos machos infectados ocorrem alterações nos espermatozoides que somente os ovócitos de fêmeas infectadas podem reverter, reestabelecendo a produtividade. Os resultados obtidos, neste trabalho, sobre a...
Keywords: Genetica molecular; Hidridação; Drosófila - Genética; Wolbachia; Fitness genético